Effects of long?term paroxetine or bupropion treatment on puberty onset, reproductive and feeding parameters in adolescent male rats - Yardımcı, Ahmet; Ülker, Nazife; Bulmuş, Özgür; Kaya, Nalan; Çolakoğlu, Neriman; Özcan, Mete; Canpolat, Sinan; Keleştimur, Haluk (My University, 2019)
Antidepressant use in adolescents has become more common in recent years. We have found several studies stating that prenatal antidepressant exposure can lead to delayed or earlier puberty onset but there was no study on postnatal paroxetine or bupropion. The main aim of this study was to investigate the effect of postnatal exposure to bupropion or paroxetine on puberty onset, reproductive and feeding results. The male rats (n = 8/group) aged 21 days were exposed to paroxetine (3.6 mg/ kg) or bupropion (17 mg/kg) orally by gastric gavage every day from postnatal day 21–90. Also, control group received only saline orally as a vehicle. Postnatal exposure to bupropion or paroxetine delayed puberty onset compared to control group, but it was not significant. Sperm counts were significantly lower in the paroxetine and bupropion groups compared to control group. Sperm motility was significantly lower in only bupropion group. In addition, sperm motility was lower in paroxetine group, but it was not significant. In the histopathological examination, there was damage to the testicular structure in both treatments. Taken together, our result indicates that postnatal paroxetine or bupropion exposure may affect puberty onset and contribute to the impairment in fertility in male rats.
Keywords: Bupropion; FSH; LH; Paroxetine; Puberty